Man-made wonders of the world - Adams, Simon, 1955- (Dorling Kindersley Limited, 2019)
Discover the most incredible statues, monuments, temples, bridges, and ancient cities, from Stonehenge to the Sagrada Familia, with this unparalleled survey of the most famous buildings and structures created by humans.